In situ green synthesis of MnFe2O4@EP@Ag nanocomposites using Epilobium parviflorum green tea extract: An efficient magnetically recyclable catalyst for the reduction of hazardous organic dyes - Gurbuz, Mustafa Ulvi; Koca, Murat; Elmaci, Gokhan; Erturk, Ali Serol (WILEY, 2021)
The present paper introduces a plant-mediated green synthesis of highly stable MnFe2O4@EP@Ag magnetically recyclable nanocomposites (MRNCs) using Epilobium parviflorum (EP) tea extract as a coating material on MnFe2O4 nanoparticles (NPs) for the Ag immobilization. Fourier transform infrared spectroscopy-attenuated total reflectance (ATR-FTIR) studies confirmed the presence of the polyphenolics in EP extract, including tannic, gallic, and other derivatives, which can enhance the complexation properties with silver ions on MnFe2O4 NPs. Thus, the capacity and the surface properties of the resulting nanosorbent (MnFe2O4@EP) can also improve their ability to form magnetic nanocatalyts without using any additional chemicals, toxic or extra-reducing agents. The transmission electron microscopy (TEM) verified the successful coating of EP extract on MnFe2O4 core as a 5 nm shell. X-ray diffraction (XRD) patterns and scanning electron microscope/energy-dispersive X-ray spectroscopy (SEM-EDX) confirmed the presence of both MnFe2O4 and crystalline silver nanoparticles in the core-shell structure of the MnFe2O4@EP@Ag MRNCs. The obtained MnFe2O4@EP@Ag MRNCs displayed high efficiency and catalytic activity for the reduction of various azo dyes like methyl orange (MO), methyl red (MR), congo red (CR), alizarin yellow (AY), nitro aromatic compound, 4-Nitrophenol (4 NP), and a common tracer, rhodamine B (RhB). Results displayed that the MnFe2O4@EP@Ag MRNCs revealed higher catalytic activity with the normalized rate constant (k(nor)) of 350.47 s(-1) g(-1) for RhB reduction. Furthermore, they were highly efficient in the reduction of other azo dyes and nitro compound in the order of MO (85.51 s(-1) g(-1)) > CR (70.09 s(-1) g(-1)) > 4 NP (62.15 s(-1) g(-1)) > AY (54.67 s(-1) g(-1)) > MR (46.73 s(-1) g(-1)). In addition, the MnFe2O4@EP@Ag MRNCs exhibited an excellent unchanged recovery efficiency even after several cycles; therefore, they can be good potential candidates for the treatment of organic pollutants in wastewater and a wide range of applications in heterogeneous catalysis.
Keywords: Epilobium parviflorum; heterogenous catalyst; magnetic recyclable nanocatalyst; organic dyes; silver nanoparticle; AZO DYES; COUPLING REACTIONS; AG NANOPARTICLES; NITRO-COMPOUNDS; WATER; BIOSYNTHESIS; NANOCATALYST; OPTIMIZATION; ADSORPTION; CHEMISTRY